A position-sensitive electronic skin based on boundary potential projection theory. Issue 1 (3rd February 2020) - Zhang, Youzhi; Lin, Zhengkang; You, Xiaojun; Huang, Xingping; Ye, Jinhua; Wu, Haibin
Abstract : Purpose: This paper aims to report a flexible position-sensitive sensor that can be applied as large-area electronic skin over the stiff media. Design/methodology/approach: The sensor uses a whole piezoresistive film as a touch sensing area. By alternately constructing two uniform electric fields with orthogonal directions in the piezoresistive film, the local changes in conductivity caused by touch can be projected to the boundary along the equipotential line under the constraint of electric field. Based on the change of boundary potential in the two uniform electric fields, it can be easy to determine the position of the contact area in the piezoresistive film. Findings: Experiment results show the proposed tactile sensor is capable of detecting the contact position and classifying the contact force in real-time based on the changes of the potential differences on the boundary of the sensor. Practical implications: The application example of using the sensor sample as a controller in shooting game is presented in this paper. It shows that the sensor has excellent touch sensing performance. Originality/value: In this paper, a position-sensitive electronic skin is proposed. The experiment results show that the sensor has great application prospects in the field of interactive tactile sensing.